The Influence of Learning Videos on Interest and Learning Outcomes Class VI Students in Mathematics SD Negeri 2 Merden Banjarnegara - Rudiarso Rudiarso; Ristiana Dyah Purwandari (Proceedings Series on Social Sciences & Humanities, 2025)
This study aims to determine the effect of Learning Videos on the Interest and Learning outcomes of grade VI SD Negeri 2 Merden in the 2023/2024 academic year. This type of research is a pseudo- experimental research with The Posttest-Only Control-Group Design. Learning interest data was collected using an assessment instrument in the form of a questionnaire and learning outcomes were measured using a description test instrument. The data were analyzed using SPSS 23 for Windows. The results showed that: First, there is a significant effect of Learning Video on the interest in learning Mathematics of grade VI students of SD Negeri 2 Merden, Purwanegara District, Banjarnegara Regency in the 2023/2024 academic year. Second, there is a significant effect of Video Learning on Mathematics learning outcomes in grade VI students of SD Negeri 2 Merden, Purwanegara District, Banjarnegara Regency in the 2023/2024 academic year. And third, there is a significant effect of Learning Videos on the interest and learning outcomes of Mathematics in grade VI students of SD Negeri 2 Merden, Purwanegara District, Banjarnegara Regency in the 2023/2024 academic year.